Pengaruh Metode Cerita Digital Dan Kartun Animasi Terhadap Pengetahuan Cuci Tangan Pakai Sabun (CTPS) Tunagrahita SLB Negeri 1 Pinrang (Window of Public Health Journal, 2025)
The process of developing a child's personality cannot be separated from the education of parents and the environment and what they see every day in socializing. One of them is people with intellectual disabilities. The method used is pre-experimental with a pre-test and post-test approach. The place of research to be conducted is in Pinrang City, South Sulawesi Province, precisely at SLB Negeri 1 Pinrang. The sample in this study was 30 respondents with 2 groups that met the criteria for people with intellectual disabilities. The results before being given education with the digital story method showed that students who had less knowledge were (66.7%). While students who had sufficient knowledge were (33.3%). Furthermore, after being given hand washing education with the digital story method, it showed that students who had less knowledge were (46.7%) while students who had sufficient knowledge were 8 (53.3%). before being given hand washing education with the animated cartoon method, it showed that students who had less knowledge were (73.3%). While students who had sufficient knowledge were 4 (26.7%). The results of the study after being given hand washing education with the animated cartoon method showed that knowledge was lacking (20.0%) while students who had sufficient knowledge were (80.0%). The conclusion of the results of this study is that before and after being given a digital story about clean and healthy living behavior, namely how to wash hands properly, the knowledge of mentally retarded children was lacking, but after being shown a digital story, the knowledge of mentally retarded children increased from before. Furthermore, the results of the study before and after being given an animated cartoon, the knowledge of mentally retarded children was still lacking, but after being shown an animated cartoon video, the respondents' knowledge increased. Animated cartoon videos have a greater influence on increasing children's knowledge than digital story videos.